Earnings by gender: evidence from Census 2000. - Weinberg, Daniel H. (Monthly Labor Review)
The article offers a look at the distribution of earnings by occupation for all year-round full-time workers in the U.S. It analyzes gender equality in terms of earnings, based on the data generated from the 2000 Census. Earnings include income from wages, salaries and self-employment. It found no significant difference in the earnings of men and women in different occupations, such as physicians, surgeons and dishwashers. The article also provides a summary of the main results of the Census 2000 Special Report.